مصطلحا ت حدیث کی تعبیر جدید: A NEW INTERPRETATION OF TERMS OF THE HADITH (Zia e Tahqeeq, 2025)
The Hadith studies remained central in Islamic tradition. The early Muhaddithin focused all their attentions to compiling and collecting the Hadith and then they devised terminologies for the assessment of Hadith. It has been observed that there is a certain degree of disagreement on various definition of a term of hadith. This paper is focused to study the various definitions of the term ‘hadith’. The Muhaddithin defined and divided the term hadith into three kinds: qawli, faili, and taqriri while the latter Muhaddithin added many other forms in the category of hadith i.e. hadith khilqi, khulqi, inshai, hikai, Makki, Madani and other compound forms. This paper provides a detailed elaboration of this term in historical perspective.